Developing Computer Science Unplugged Worksheets to Enhance Second-Grade Number Concept Understanding - Titik Purnamasari; Raden Sulaiman; Ali Shodikin (Journal of Mathematics Education and Science, 2026)
This study aimed to develop and evaluate Computer Science Unplugged (CS Unplugged)–based student worksheets to enhance second-grade students’ understanding of number concepts. This study employed a Research and Development approach using the ADDIE model and involved 26 second‑grade students in a limited practical trial. The developed worksheets were evaluated through expert validation, practicality testing based on teacher and student responses, and effectiveness testing using a one-group pretest–posttest design. The results indicated that the worksheets achieved a very high level of validity (media: 92.67%; content: 91.67%) and practicality (students: 91.38%; teacher: 90%). The effectiveness test showed a substantial improvement in students’ learning outcomes, with the mean score increasing from 67 in the pretest to 90.38 in the posttest, and an N-gain score of 0.73, categorized as high. These findings demonstrate that CS Unplugged–based worksheets are valid, practical, and effective for improving students’ understanding of number concepts while supporting the integration of computational thinking in elementary mathematics education.